The Ergonomic Intervention for Musculoskeletal Diseases and Pain among Oral Health Therapist - Sunarjo, Lanny; Fatmasari, Diyah; Rahmadhani, Febby (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Musculoskeletal diseases and pain (MSDs) is commonly occurred among oral health therapist due to improper working positions. This condition can lead to work-related accidents, lower job satisfaction, and increased healthcare costs. In order to address this issue, ergonomic interventions encompassing cognitive, physical, and organizational aspects have been recommended to prevent the occurrence of MSDs. This study aims to assess the effectiveness of ergonomic interventions, specifically using the